THE EFFECT OF BINDERFLOUR SUBSTITUTION OF TAPIOCA WITH DURIAN(Durio zibethinus murr) AND JACKFRUIT (Artocarpus chempeden)SEEDS FLOUR ON THE QUALITY OF CATFISH (Clarias gariepinus)MEATBALLS STORED AT COLD TEMPERATURE (5°C) - Hermanto, Putra Rio; Sari, N Ira; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this research was to know the effect of using combination of durian seeds flour (Durio zibethinus murr) and jackfruit seeds flour (Artocarpus chempeden) as the binder flours to substitute tapioca flour on quality of catfish(Clarias gariepinus) meatballs stored at cold temperatures (5°C). This research was using randomized block design composed factorially in experimental method. The treatment conducted was consisted of 2 level combination, namely: (H0without a binderdurian seed flour and jackfruit seed flour, as a control) and (H1 with a binder combination of 10% durian seed flour and 30% jackfruit seed flour). The parameters tested were organoleptic and chemical. The results showed that substitutionof tapioca flour with combination durian seed flour and jackfruit seed flour was indicated the best quality. The value of the organoleptic score of. catfish meatballs was 8,01 and had the shelf-live for 12 daysstored at cold temperature (5°C). The fish meatball contained 6,36% protein and 75,17% moisture. It could be concluded that the durian seeds flour and jackfruit seeds flour can substitute tapioca flour.Keywords: Catfish, durian seed flour, jackfruit seeds flour, meatballs, tapioca flour